Job Satisfaction and Turnover Intention: The Moderation Role of Financial Compensation - Jason Aji Widyanata; Christantius Dwiatmadja (Quantitative Economics and Management Studies, 2024)
In managing Human Resources in a company, a leader must be able to handle the phenomenon of turnover intention. Turnover intention is a problem that arises in an organization involving the desire to leave employees. The turnover intention that occurs indicates low employee loyalty and a weak managerial system in the company. This research aims to examine the influence of job satisfaction variables on the turnover intention phenomenon and examine the role of financial compensation variables in moderating the influence of job satisfaction variables on the turnover intention phenomenon. The type of research used in this research is explanatory research. Sampling in this research was carried out using a purposive sampling technique or non-random sampling technique. The sample in this study involved 90 employees at PT. HM Sampoerna Semarang, all of which met the criteria to be used as samples. The data source in this research is primary data in the form of a questionnaire. The type of data in this research is cross section. In the research, it was found that the job satisfaction of each employee is relatively high, one of the factors that triggers turnover intention in this company is job satisfaction. The research results show that there is an influence between job satisfaction variables on turnover intention, and financial compensation cannot be a moderating variable or a supporting factor in the influence of job satisfaction on turnover intention at PT. HM Sampoerna Semarang.